2020
DOI: 10.1080/03066150.2019.1708724
|View full text |Cite
|
Sign up to set email alerts
|

Neither sustainable nor inclusive: a political economy of agricultural policy and livelihoods in Malawi, Tanzania and Zambia

Abstract: The food crisis of 2007/8, alongside rapid population growth, and the uncertainties of climate change propelled African agricultural transformation back into the development mainstream. New narratives of 'climate-smart agriculture' and 'sustainable intensification' underlie this contemporary transformation. We present a political economy analysis of agricultural policy and livelihoods in Malawi, Tanzania and Zambia, and use this to assess the challenge of achieving 'sustainable and inclusive intensification'. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(75 citation statements)
references
References 85 publications
(117 reference statements)
0
45
0
Order By: Relevance
“…Even where farmers are linked to agribusinesses as suppliers, benefits are not guaranteed in part due to power dynamics (Manda et al 2018a). Cooperatives have for a long time been relied upon across Africa, but this study finds no concrete evidence that this help to address smallholder challenges (except in rare cases of subsidies which remain politically productive) (Mdee et al 2020). In the case study area, cooperatives were narrow as opposed to being broad based, failing to provide necessary production and marketing information, storage facilities, and advocating for infrastructure development (of course a tall ask).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Even where farmers are linked to agribusinesses as suppliers, benefits are not guaranteed in part due to power dynamics (Manda et al 2018a). Cooperatives have for a long time been relied upon across Africa, but this study finds no concrete evidence that this help to address smallholder challenges (except in rare cases of subsidies which remain politically productive) (Mdee et al 2020). In the case study area, cooperatives were narrow as opposed to being broad based, failing to provide necessary production and marketing information, storage facilities, and advocating for infrastructure development (of course a tall ask).…”
Section: Discussionmentioning
confidence: 80%
“…General political, donor and NGO narratives in Zambia promote smallholder value chain integration and participation in market linkages (Manda et al 2020). Interviews with extension officers explained that "these pronouncements might be true at policy level, but the reality on the ground is that our farmers face challenges to access marketing linkages and platforms" (Interview, Kitwe).…”
Section: Marketing Opportunities and Challenges Among Small-scale Producersmentioning
confidence: 99%
See 1 more Smart Citation
“…This is mainly due to mistargeting and implementation issues in the programme. According to Mdee et al (2020), based on input subsidy programmes Malawi, Zambia, and Tanzania, agricultural institutions do not have the ability to sustain intensification in agriculture. Further, Gilbert (2020) showed that not all countries in sub-Saharan Africa have been able to increase uptake of improved seeds and the number of farmers using inorganic fertilizer, and that input subsidy programmes have not achieved their objectives.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The findings will help policy makers and development partners to understand the dynamics behind the outcome of this programme. Furthermore, the findings will inform any future efforts to implement agricultural subsidy programmes in Tanzania and similar contexts in sub-Saharan Africa (see Gilbert 2020;Mdee et al 2020).…”
Section: Introductionmentioning
confidence: 98%